TelomereHunter: in silico estimation of telomere content and composition from cancer genomes - Feuerbach, Lars; Sieverling, Lina Katharine; Deeg, Katharina; Hutter, Barbara; Buchhalter, Ivo; Mughal, Sadaf Shabbir; Chudasama, Priya; Glimm, Hanno; Scholl, Claudia; Lichter, Peter; Fröhling, Stefan; Pfister, Stefan; et al. (BMC bioinformatics, 2019)
Establishment of telomere maintenance mechanisms is a universal step in tumor development to achieve replicative immortality. These processes leave molecular footprints in cancer genomes in the form of altered telomere content and aberrations in telomere composition. To retrieve these telomere characteristics from high-throughput sequencing data the available computational approaches need to be extended and optimized to fully exploit the information provided by large scale cancer genome data sets.
Gesehen am 09.07.2019